The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/1465-9921-12-130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of epithelial mesenchymal transition in patients with chronic obstructive pulmonary disease

Abstract: BackgroundThe reticular basement membrane (Rbm) in smokers and especially smokers with COPD is fragmented with "clefts" containing cells staining for the collagenase matrix-metalloproteinase-9 (MMP-9) and fibroblast protein, S100A4. These cells are also present in the basal epithelium. Such changes are likely hallmarks of epithelial mesenchymal transition (EMT). We aimed to confirm the epithelial origin of these Rbm cells, and to exclude potential confounding by infiltrating inflammatory cells.MethodsEndobronc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
97
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 28 publications
6
97
0
Order By: Relevance
“…EMT in conducting airways was shown in post-transplant bronchiolitis [25], as well as in chronic rhino-sinusitis [26]. In COPD, SOHAL and colleagues [12,13] observed in large airways from COPD patients the presence of clefts within the RBM containing S100A4/vimentin/ matrix metallopeptidase (MMP)-9 positive epithelial cells, presumably migrating from the surface epithelium to the lamina propria. MILARA et al [14] recently reported EMT features in small airways of smokers and COPD patients and in undifferentiated (submerged) primary broncho-epithelial cells from COPD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMT in conducting airways was shown in post-transplant bronchiolitis [25], as well as in chronic rhino-sinusitis [26]. In COPD, SOHAL and colleagues [12,13] observed in large airways from COPD patients the presence of clefts within the RBM containing S100A4/vimentin/ matrix metallopeptidase (MMP)-9 positive epithelial cells, presumably migrating from the surface epithelium to the lamina propria. MILARA et al [14] recently reported EMT features in small airways of smokers and COPD patients and in undifferentiated (submerged) primary broncho-epithelial cells from COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…EMT participates in normal lung biology during development (airway branching) and repair, but is also observed during cancer progression and metastasis [10]. While alveolar EMT has been reported in lung fibrosis [11], three recent studies suggest that EMT also occurs in COPD airways [12][13][14]. However, the underlying mechanisms and the functional consequences of EMT in the conducting airways from COPD patients remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, evidence for EMT in the large airways of smokers and patients with COPD has been suggested by Sohal and colleagues, since cells included in the reticular basement membrane of large airways showed EMT markers 13. However, whether EMT is present in the small airways of smokers and patients with COPD and whether cigarette smoke directly induces EMT in differentiated HBECs remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In a follow-up paper3 we excluded such confounding. Further, our study illustrated that cells in the basal epithelium, and reticular basement membrane (Rbm) in smokers/COPD double-stain for cytokeratin-(s) and the ‘EMT marker’ S100A4, confirming a likely epithelial origin of these cells.…”
mentioning
confidence: 99%